Meta‐governance and network formation in collaborative spaces of uncertainty: The case of Swedish refugee integration policy. (27th February 2017) - Qvist, Martin
Abstract : This article examines the relationship between a meta‐governing role of government and processes of network formation, based on a study of a governance initiative for improvement of refugee 'activation' services in Sweden. Meta‐governance is centred on supporting the development of self‐regulatory capacity within discretionary spaces of action and has, so far, primarily been associated with a specific type of interdependency‐driven networks. This article focuses on an alternative scenario, where uncertainty under such governance arrangements, rather than interdependence, becomes the driver of network formation. The relevance of this 'uncertainty approach' is demonstrated in the Swedish case, where meta‐governance resulted in networks that were formed on the basis of identification rather than organizational complementarity, and contributed to increasing homogenization rather than local adaption of activation services. The result suggests that theories of meta‐governance should include a more diversified understanding of network responses.